Detection of rabies virus genome in brain tissues by using in situ hybridization - REDDY, CH CHAKARAVARTHY; JAYAKUMAR, R; KUMANAN, K; NAINAR, A MAGALINGA (The Indian Journal of Animal Sciences, 2014)
Rabies virus is usually demonstrated in brain tissues by antigen detection. In the present study an attempt was made to detect rabies RNA in paraffin embedded tissues using in situ hybridization. Brain samples (69) from rabies suspectedanimals and 15 brain samples from experimentally inoculated mice (with street rabies strain) were screened first by fluorescent antibody test (FAT) and then by in situ bybridization (ISH) using digoxigenin labelled nucleic acid probes compared with the standard FAT. ISH gave good cellular localization signals in positive slides. ISH has potential ability in studying rabies pathogenesis and in gene expression studies.